Investigation on the lignite pyrolysis reaction kinetics based on the general Arrhenius formula. (15th May 2020) - Lian, Wenhao; Wang, Junli; Wang, Guijing; Gao, Deyang; Li, Xue; Zhang, Zhonglin; Huang, Wei; Hao, Xiaogang; Hou, Baolin
Abstract: Studying the reaction kinetics can deepen the understanding of reaction mechanism and provide a relatively accurate and efficient reaction rate expression to theoretically optimize the relevant reactor. Here, the complicated lignite pyrolysis was assumed to be performed by the multi-parallel first order reactions, and the kinetic parameters of Arrhenius formula for each first order reaction were obtained through fitting the thermogravimetry (TG) experimental data. Thus, our developed kinetics models can avoid the multiple integration of using the well-known distributed activation energy model (DAEM) in evaluating the pyrolysis rate, the computational time for predicting the pyrolysis in a single lignite particle is reduced from 51.9 s to 3.8 s, which is important for theoretically optimizing the reactor, especially for using the well-developed computational fluid dynamics (CFD) theory. And, the simulating results showed that the developed kinetics model can more accurately predict the lignite pyrolysis process than that of DAEM.